Utilisation of maternal healthcare services and influencing factors in public health facilities in Addis Ababa, Ethiopia - Sintayehu A. Temesgen; Thinavhuyo R. Netangaheni (AOSIS, 2024)
Background: Ethiopian maternal mortality remains high, despite the implementation of extensive health programmes. This indicates that the full potential of maternal health services is not being effectively utilised. Aim: This study aimed to evaluate the utilisation and factors influencing maternal healthcare services in public health facilities in Addis Ababa. Setting: This study was conducted in five public hospitals and 10 public health centres of Addis Ababa city administration from 31st August 2023 to 13th October 2023. Methods: The study's design utilised a cross-sectional quantitative technique, which involved interviewing 354 women from each group who received visits throughout their pregnancy, delivery and postpartum period. The data were analysed using SPSS version 26. Results: This study analysed maternal health service utilisation indicators, revealing a 70.8% overall utilisation of services, with antenatal care (ANC) at 85.5%, delivery at 71.58% and family planning services (PNC) at 55.4%. The study found that the length of time spent travelling to public health facilities significantly impacts the use of maternal health services. Pregnant women who travelled less than 30 min used services 2.29 times more than those over 2 h. The average client wait time also influenced service usage. Pregnant women with four or more prenatal care visits were more likely to use services. Conclusion: The study conducted in Addis Ababa's capital city revealed that the utilisation of maternity health care services is not optimal, despite the concentrated resources. Contribution: The findings of the study could be beneficial for the Addis Ababa Health Bureau, Ministry of Health, legislators, and other stakeholders. It can help in the development of affordable intervention programmes, filling knowledge gaps and updating scientific understanding.